â€œIMAGINE YOURSELFâ€ BEING A DIGNIFIED NATION: A PRELIMINARY ASSESSMENT - Krisnadi, Ignatius (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
This paper is constructed in the purpose to identify the Javanese local wisdom in order to develop a dignified Indonesian nation. Discussion on this paper will cover several issues as follows: identification of the Javanese local wisdom of the previous era, the broken down of society order due to Western culture penetration, and cultural strategy for the purpose of developing a dignified Indonesia.Success in identifying the Javanese local wisdom and causal factors of the Javanese society disorder, as well as the way out ofÂ kalabenduÂ era, can be used as references to form cultural strategies in order to develop the dignified Indonesia. The cultural strategies mentioned are as follows: national repentance (National Reconciliation), law enforcement, the clean, honest, impartial and prestigious governmentâ€™s implementation, cultural movement of corruption eradication, inistilling the sense to value the domestic products and proud to be Indonesian, instilling the culture of being ashamed of doing something improper, science and technology development based on well-mannered, law, and humanity norms, and build social ethos based on religion.Â